Evaluasi Kritis Proses Produksi Gula Aren Melalui Pendekatan FMEA – Risk Matrix - Azzumardi, Nispi; Hidayat, Ananda Syalsabila; Mahendra, Yusril Iza (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2025)
Traditional palm sugar production faces various risks such as material contamination, occupational accidents, and procedural inconsistencies that reduce product quality and production safety. Indonesia’s national sugar trade deficit reached 5 million tons in 2023, highlighting the urgent need for risk mitigation in this sector. This study aims to identify, measure, and prioritize risks across 22 stages of the palm sugar production process using the FMEA–Risk Matrix approach, supported by mitigation strategies focused on occupational safety and product quality. A descriptive research method was applied through field observations and interviews. Each potential risk was evaluated using Severity, Occurrence, and Detection scores and then mapped using the Risk Matrix. The analysis identified five main risks, with the highest RPN found in the risk of animal or ant bites (R4 = 175), followed by injury from cutting tools (R5 = 112) and falling from trees (R3 = 96). Most risks were categorized as medium (45%), followed by low (39%) and high (16%). The most dominant mitigation efforts (61%) included routine container cleaning, use of heat-resistant clothing and Kevlar gloves during cooking, and daily monitoring of PPE compliance with a minimum target of 90%. This integrated approach effectively identifies and prioritizes risks in palm sugar production, while enhancing worker safety and product quality. The use of heat-resistant PPE and hygienic procedures has been proven to significantly reduce burn injuries and material contamination. This study expands the application of industrial risk management to traditional agroindustry, offering a measurable mitigation model for palm sugar production and supporting efficiency and sustainability in the national sugar supply chain.